Effect of Salinity Variation on Survival of Pearl Oyster Spawn (Pinctada maxima) - Padalegi, Maria; Tjendanawangi, Agnette; Suleman (MultiTech Publisher, 2024)
Pearl oysters (Pinctada maxima) are a high-value fishery commodity with significant development prospects, due to increasing demand and selling value in domestic and international markets. One of the challenges in pearl oyster cultivation is determining the optimal salinity to improve spat (seed) survival. This study aims to evaluate the effect of various salinity levels on the survival of Pinctada maxima spat and determine the optimal salinity. The study used a completely randomized design (CRD) with four salinity treatments: 35 ppt, 30 ppt, 25 ppt, and 20 ppt, each with three replicates. Results showed that the highest survival rate was found at 35 ppt (63%) and 30 ppt (23%) salinity, while the lowest survival rate was at 25 ppt (7%) and 20 ppt (1%) salinity. Salinity of 35 ppt gave the best results for survival and weight growth of pearl oyster spat, followed by salinity of 30 ppt. These findings have important implications for the development of more effective and efficient culture methods to improve pearl production and quality.